International approaches to hydrocarbon development in disputed zones : unitization and unit operating agreements - Pereira, Eduardo G.; Pappa, Marianthi; Olawuyi, Damilola S. (Damilola Sunday), 1983- (Abingdon, Oxon [UK] ; New York, NY : Routledge, 2024)
"This book analyses the legal obstacles associated with the advancement of unitization processes and procedures at an international level. Using case studies in international (cross border) unitization and joint development agreements, the book uses regional examples from the Americas, Europe, Africa and Middle East. It will also touch upon case studies related to ongoing disputes from the South China Sea, Mediterranean Sea and Gulf of Guinea. Focusing on best practices which have influenced the development of the unitization concept, the book looks at the formulation of different models and agreements, and their potential impact on unexplored hydrocarbon resources, particularly in cases where unitization is necessary. The book will be of interest to practitioners, scholars and students in the field of natural resource law, international law and unitization"--
General Introduction / Eduardo G. Pereira, Marianthi Pappa and Damilola S. Olawuyi -- Cross-Border Unitization and Joint Development / Eduardo G. Pereira, Marianthi Pappa and Damilola S. Olawuyi -- Exploitation of Transboundary Hydrocarbon Reservoirs : Rules in the Americas / Maria Serna and Alicia Elias-Roberts -- Cross Border Unitization and Joint Development Zones : Case Studies from Africa / Mark K. Amakoromo, Rukungo S. Muhongo, and Eduardo G. Pereira -- European Cross Border Unitization Agreements : A Case Study of the UK, Norway and the Netherlands / Dickson E. Omukoro and Azubuike Ozah -- Unitization in the Middle East Oil and Gas Sector / Elena I. Athwal -- International Boundary Disputes in Africa : Perspectives from Africa's Great Lakes Region / Opeyemi Omotuyi -- Joint Development of Petroleum Resources in the East and South China Seas / Fayokemi Olorundami -- The Mediterranean Sea / Marianthi Pappa and Hussein Badreddine -- Negotiating Risk-Free Unitization and Joint Document Agreements : Summary and Options for Policymakers / Eduardo G. Pereira, Marianthi Pappa, and Damilola S. Olawuyi.
Keywords: Hydrocarbon reservoirs -- Law and legislation; Unit operation of oil fields; Petroleum law and legislation; Gas -- Law and legislation; LAW / International; LAW / Natural Resources; LAW / General